DOES PERCEIVED DISCRIMINATION AFFECT JOB SATISFACTION AMONG TEACHERS AND STAFF? - Devani Laksmi Indyastuti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2019)
Previous research have not paid much attention on the the mechanism of the relationship between perceived discrimination and the negative outcomes. This research examined the relationship between perception of discrimination and job satisfaction, as well as how basic psychological need satisfaction can play the role in that relationship. This study used teachers and the staff in Purwokerto for the sample. This study used purposive sampling. We choose teachers and staff that have three year experience. This study used individual level of analysis. The result showed that perceived discrimination negatively affects autonomy, relatedness and job satisfaction, but not competence. The relationship between perceived discrimination and job satisfaction was mediated by autonomy. Autonomy positively affects job satisfaction, but not both relatedness and competence. Future research should examine this relationship in other context, for example the bank employees, manufacturer, nurses, etc. Future research also need to examine this relationship that use experiment design to increase internal validity.